Gateway Redundancy Using Common Address Redundancy Protocol (CARP) - Rini Nur; Zawiyah Saharuna; Irmawati Irmawati; Irawan Irawan; Reski Wahyuni (IJITEE (International Journal of Information Technology and Electrical Engineering), 2019)
Gateway redundancy can ensure the network availability and reliability in providing a service. One way is to make a backup system on the gateway. This backup system can be applied to the router so that if a failure occurs on the master router its task and function can be transferred to the slave router. The transition process from master router to slave router is known as failover. Common Address Redundancy Protocol (CARP) is one of the redundancy gateway protocols and provides a failover mechanism on the router. Therefore, this study will analyse the CARP protocol implementation in ensuring the network services availability by measuring parameters of throughput, delay, retransmission, and downtime. The results showed that CARP implementation on the network produced the throughput, delay, and retransmission values of 61.7 Mbps, 0.14 ms, and 1.11% when without the link termination and 18 Mbps, 0.53 ms, and 1.58% when with link termination, while the downtime value is 2.91 seconds. The QoS test results show good quality based on ITU-T.